Toxicity assessment of engineered and airborne process-generated nanoparticles in human alveolar epithelial A549 cells - Bessa, Maria João (2019)
Nanotechnology offers many possibilities in the ceramic sector by providing innovation of the industrial processes and products. However, nanoparticles (NPs) used in the manufacture of ceramic goods or released to the workplace air during production may pose a serious hazard for human health. This study aimed to investigate in vitro toxicity of both engineered (ENPs) (ZrO2, CeO2, SnO2 and Sb2O3•SnO2) and process-generated nanoparticles (PGNPs) [released during High Velocity Oxy-Fuel (HVOF) spraying] in human alveolar epithelial cells, a primary target following inhalation exposure.